Viewing Mexican Tradition of “Dia De Los Muertos” in The Animation Film “Coco” - Ramadianti, Rahma Putri; Tarmawan, Irwan (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
Coco Animation Film is one of the animations that displays a typical Mexican tradition, namely "Dia de Los Muertos" or the feast of the dead. In general, this film shows how the culture of Mexicans believes in the feast of the dead. In addition, the film shows the holiday from the perspective of those who have died. The purpose of this study is to further examine the beliefs of Mexicans in describing what happens after death. The research method used in this study uses qualitative methods, namely research that tends to use analysis where the data that has been collected will be studied further. Data comes from text studies or literature studies. The results of this study indicate that this hereditary belief or tradition is very close to Mexican society and has become their identity. On this holiday, it is tradition for the family to display photos, serve food, drinks and activities that the deceased person likes. The things that are served become very synonymous with Mexican identity because they usually feature typical Mexican visuals and audio.